2015
DOI: 10.1111/aec.12233
|View full text |Cite
|
Sign up to set email alerts
|

Seed size and the regeneration niches of one rare (Melaleuca deanei) and three common (Melaleuca styphelioides,Melaleuca thymifoliaandMelaleuca nodosa)Melaleuca(Myrtaceae) species of theSydney region

Abstract: Seed size and the regeneration niches of one rare (Melaleuca deanei) and three common (Melaleuca styphelioides, Melaleuca thymifolia and Melaleuca nodosa) Melaleuca (Myrtaceae) species of the Sydney region Abstract Melaleuca species occupy varied habitats across Australia with 16 members of the genus occurring in the Sydney district including the rare species Melaleuca deanei F. Muell. Little is known of their germination and recruitment requirements. This paper reports on experiments assessing the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Consistent with previous germination studies in M. quinquenervia (Rayachhetry et al 1998; Van et al 2005), and the genus more broadly (Robinson et al 2006;Hewitt et al 2015), this study showed little difference between germination figures and viability figures.…”
Section: Seed-burial Longevity Trialsupporting
confidence: 92%
“…Consistent with previous germination studies in M. quinquenervia (Rayachhetry et al 1998; Van et al 2005), and the genus more broadly (Robinson et al 2006;Hewitt et al 2015), this study showed little difference between germination figures and viability figures.…”
Section: Seed-burial Longevity Trialsupporting
confidence: 92%
“…Fire also triggered seed release en masse in the field from a strongly serotinous canopy seed bank, with seed noted to then germinate readily within larger populations following rainfall. However, in all populations monitored, seedlings failed to survive longer than one year, with soil moisture adequate for germination and seedling survival apparently critical (Virtue ; Hewitt et al and and observations since).…”
Section: Resultsmentioning
confidence: 98%
“…Melaleuca deanei displayed similar germination parameters to four common congeners, despite its occurrence over relatively drier substrates (Hewitt et al ). The root suckering and paperbark covering of the roots of M. deanei appear also to be adaptations for the more periodically waterlogged environments that are believed to be ancestral to Melaleuca and in which many present‐day members of the genus occur (Lamont ; Barlow ; Brophy et al ; Edwards et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been investigating whether common species with broader distributions possesses patterns of seed traits and germination characteristics that favor their occurrence compared to more narrowly distributed close relatives (Lavergne et al 2004;Mattana et al 2010;Youssef et al 2011;Imbert et al 2012). For instance, Paulů et al (2017) found significant differences in seed mass, while other studies showed that rare species could possess either lighter or heavier seeds than their common congeners (Brown et al 2003;Hewitt et al 2015). There is no consensus about possible patterns of species distributions determined by seed features since patterns are largely species-specific (Paulů et al 2017).…”
Section: Introductionmentioning
confidence: 99%